Analisis Ketidakstabilan Beban Arus Netral dan Rugi-Rugi Daya Pada Trafo Distribusi Penyulang Pas 21 PT. PLN UPB Banda Aceh - Suriadi; Sara, Ira Devi; Syuhada, Ahmad; Masri; Asri; Umurani, Khairul (Yayasan Kawanad, 2023)
This research focuses on analyzing power losses due to load imbalance in the medium-voltage distribution network in Pasar Aceh. The aim is to determine the magnitude of power losses that occur at the distribution substation in Pasar Aceh. The research method involves analysis, calculations, and simulations using the ETAP 12.6 software. The results of the analysis indicate that load imbalance in the Pasar Aceh substation leads to power losses. The Trafo Samping Pasar Aceh experiences power losses of 0.77% with a load imbalance of 16.33%. The second transformer in the BNI 46 area incurs power losses of 0.98% with a load imbalance of 30.33%, and the transformer in the BLKG KOTTY area has power losses of 1.17% with a load imbalance of 50.33%. These findings affirm that the greater the load imbalance, the higher the resulting power losses in the electrical distribution network.